Microsatellite Diversity of Androgenic Black Poplar (Populus nigra) - Bittsánszky, András; Gyulai, Gábor; Kiss, József; Gullner, Gábor; Heszky, László; Kőmíves, Tamás (Acta Agraria Debreceniensis, 2007)
Genetic variation of somatic clones (1 to 35) of black poplar (Populus nigra) developed from two anther-donor trees N-SL and N-309 was determined by five SSR primer pairs. Twenty SSR alleles were detected, the number of alleles per marker ranged from 1 to 6, with an average of 3.3 including WPMS-2 (5 alleles), WPMS-4 (6 alleles), WPMS-6 (2 alleles), WPMS-20 (6 alleles) and PTR-4 (1 allele) detected by ALF (automatic laser fluorometer). Adendrogram produced by SPSS11 based on the presence versus absence of SSR alleles discriminated the groups of somatic clones of N-SL from somatic clones of N-309. The polymorphic markers of WPMS-2 (5 alleles), WPMS-4 (6 alleles) and WPMS-20 (6 alleles) revealed clonal variation in 1 clone (37) out of the 6 from the N-309 tree, and three subgroups out of the 29 somatic clones from the N-SL tree (17 and 24), (2 and 14) and (10 and 15). The remaining 23 of the 29 N-SL somatic clones with uniform genetic similarity suggests a good degree of genetic stability in black poplar. Nevertheless, the new SSR-clones may provide useful new genetic resources for poplar breeding.